Implementasi Algoritma Hybrid Depth-First Search dan Breadth-First Search pada Sistem Repository Dokumen Hasil Karya Mahasiswa (Studi Kasus Pada Jurusan Teknologi Informasi Universitas Tadulako) - Ardiansyah, Rizka (Fakultas Teknik, Universitas Tadulako, 2018)
Departement of Information Technology Tadulako University, currently does not have a digital repository system that can accommodate the work of student either in form of paper, research report, and scientific posters at the moment. Various of student works is stored in form of physical archives which is definitely risky to get damaged, lost, difficult to access by other students. The existence of a digital repository system can also be used as a benchmark media to develop student creativity in producing scientific work. Searching mechanism is one of the crucial parts in a repository system. There are several commonly used algorithms such as Depth-First search and Breath-First search. Each algorithm have deficiencies and advantages. Therefore, to optimize the searching mechanism on the proposed digital repository system, the author purpose using the DepthFirst search and Breath-First search hybrid algorithms. The result of this study are the design of a prototipe repository system that able to manage and store student scientific documents archive digitally. This system also has a fast and accurate data search fiture.